Eksistensi Program Kampus Mengajar Angkatan 5 Terhadap Hasil Belajar Pada Peserta Didik SDN Plosorejo 2: The Existence of Campus Teaching Program Batch 5 on Learning Outcomes in Students of SDN Plosorejo 2 - Anggraini, Ari Saputri Novita; Surindra, Bayu (Efektor, 2023)
Students from various backgrounds are joining Kampus Mengajar 5 (teaching campus programs) to support and assist teaching activity programs in elementary and junior high schools. Kampus Mengajar is one of the programs from Kampus Merdeka. The existence of Kampus Mengajar is expected to help improve student abilities in literacy and numeration. This research used comparative analysis with the aid of SPSS software. The sample used in this research is a saturated sample. The existence of Kampus Mengajar batch 5 at SDN Plosorejo 2 has shown significant growth. There are comparisons of results studied with students before and after the existence of Kampus Mengajar batch 5. The result of students learning before being approached by Kampus Mengajar batch 5 was 81.81. While the learning result of student after Kampus Mengajar batch 5 increased by 88.26.